PENERAPAN HAK MENDAPATKAN BIAYA PENGGANTI PADA SAKSI BERDASARKAN KUHAP DI WILAYAH HUKUM PENGADILAN NEGERI PEKANBARU - Marbun, Maruli Tua; Diana, Ledy; ', Erdianto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Law was created to regulate the order of people's lives and to protect all components of a civilization. But lately laws in Indonesia gained sharp spotlights from all levels in the society. This happens because the law that is expected to be a regulating instrument, balancing tool between public and individual interests, and a driving catalyst to enhance the change processes to protect a community, is far off the expectation. Under the provisions of Article number 184 paragraph 1 of the Book of the Code of Criminal Procedure (KUHAP) explains that there are valid instruments of evidence that can be used in a court that including: description of witnesses, experts, information letters, instructions, and descriptions of defendant. Evidence of witnesses has an important role in uncovering the truth of material of a crime. In Article 229 paragraph 1 of the Criminal Code also mentioned that there is a right for a grant or a replacement cost for a witness or an expert who avowed to present at the hearing. Nonetheless, in the reality this right has not been fulfilled successfully.The objectives of this research paper therefore are: first, to know how is the implementation of the right to obtain a replacement fee for the witnesses in District Court of Pekanbaru according to the book of the code of criminal procedure (KUHAP); second, to know what are the obstacles in implementing this right; and third, to know what are the feasible solutions that can be done to put this right into practice effectively.The type of research done in this research was empirical juridical or legal sociological research. It was conducted at the state court and the state prosecutor of Pekanbaru. Sources of data used were primary, secondary, and tertiary. The technique of data collection was by literature research in library and direct interviews with various group of professionals and authorities. Data analysis was eventually analyzed by a deductive data method. The results of this research were: first, the practice of the law of allocating a replacement fee to witnesses in Pekanbaru was not effectively executed as the number of obstacles in practice is still high. Second, the obstacles found in implementing this right include: the lack of financial management in the court; lack of coordination and communication between the court and the prosecutor office; the lack of enforcement agency to monitor and control the activities of law implementation. Nevertheless, the people as the users of the law are ultimately unaware of the right that would benefit and protect themselves. Third, efforts that can be undertaken by the law enforcement agencies, especially in Pekanbaru area, are by proposing additional operating cost of the court, establishing cooperation and coordination with other relevant agencies, and increasing the frequency on education and socialization of the right to the respective people.Keyword: Application of Rights, Replacement Costs, Witness